PERENCANAAN STRATEGI PEMBELAJARAN PAI BERBASIS PROYEK DAN RESOLUSI KONFLIK - Muh Rezky; Dika Tripitasari; Ahdar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to formulate a strategic plan for Islamic Religious Education (PAI) learning that integrates the Project-Based Learning (PjBL) model with the strengthening of students' conflict resolution skills. In the era of globalization, PAI faces the challenge of shaping multicultural characters capable of maintaining harmony amidst diversity. The method employed is descriptive qualitative through a literature study, analyzing sources related to instructional innovation, conflict management, and the reinforcement of religious moderation values. The research findings indicate that PjBL planning in PAI not only enhances cognitive understanding but also serves as a vehicle for internalizing moderation values through collaborative projects. The integration of conflict resolution within this strategy includes preventive measures through collaborative leadership and the creation of a positive learning environment. Students are trained to identify problems, communicate openly, and seek peaceful solutions to differences of opinion that arise during project execution. The alignment between a structured PjBL design and conflict management based on Islamic values is proven effective in improving social-emotional skills and building a tangible attitude of tolerance (tasamuh) in daily interactions at school.